2014
DOI: 10.1177/0192512114559108
|View full text |Cite
|
Sign up to set email alerts
|

Political trust, extra-representational participation and the openness of political systems

Abstract: The relationship between trust in representative political institutions and extra-representational participation (ERP) is contested. Generally, scholars have assumed that distrust is a major source of ERP. However, empirical studies have yielded inconclusive results. This article contributes to the debate by linking it to recent studies on how contextual factors affect the amount of ERP and interact with micro-level predictors. We take an innovative stance by conceptualizing the openness of political systems i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
44
0
13

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(68 citation statements)
references
References 38 publications
(62 reference statements)
6
44
0
13
Order By: Relevance
“…In the case of distrust in institutions, the study of Braun and Hutter (2014) confirms previous studies which showed that participation is more common among those citizens more distrustful (Anderson & Mendes, 2006;Dalton et al, 2009), but also reveals that the negative relationship between trust and collective action is even greater in those systems politically more open. According to Anduiza, Cristancho, and Sabucedo (2014), Occupy/Indignados movement follows protests in France and Greece and is a reaction against the inability of the system to address the economic and social problems of their citizenship.…”
Section: Attitudes Towards Political Systemsupporting
confidence: 83%
“…In the case of distrust in institutions, the study of Braun and Hutter (2014) confirms previous studies which showed that participation is more common among those citizens more distrustful (Anderson & Mendes, 2006;Dalton et al, 2009), but also reveals that the negative relationship between trust and collective action is even greater in those systems politically more open. According to Anduiza, Cristancho, and Sabucedo (2014), Occupy/Indignados movement follows protests in France and Greece and is a reaction against the inability of the system to address the economic and social problems of their citizenship.…”
Section: Attitudes Towards Political Systemsupporting
confidence: 83%
“…Hutter, S. (2016) regarding political trust and political participation. For instance, they cited that many studies revealed that being involved in political activities do not directly relate to political trust.…”
Section: Discussionmentioning
confidence: 99%
“…Which parties benefit? Much has been written about the impact of political dissatisfaction on protest (Braun and Hutter, 2016;Christensen, 2014). Yet, the evidence on the impact of political disaffection on electoral behaviour remains scarce.…”
Section: H1 -Disaffection Explains (Correlates) Electoral Choices In mentioning
confidence: 99%